Building Complaint Handling Mechanisms For Effective Leadership - Pramusinto, Agus (UI Scholars Hub, 2014)
This paper discusses complaint handling mechanisms local leaders use for effective leadership. In a democratic government, public policy formulation is supposed to represent the interests of the citizens through a democratic political process. However, the involvement of the citizens is also needed during the public service delivery. A number of local leaders have built various complaint handling mechanisms tailored to channeling the voices of their citizenry. For example, the Mayor of Yogyakarta City established Walikota Menyapa (Mayor’s Greeting) as medium of outreach and communication with people under his jurisdiction. The question is: Do such mechanisms contribute to effective leadership? In this regard, how do citizens use the mechanisms in expressing their aspirations and concerns and how does the Mayor respond to the complaints he receives from his citizens?. The research used documentary analysis method. Walikota Menyapa (WM) program reports were analyzed by quantifying the data. Qualitative analysis was also used to decipher the content of the complaints citizens made. The data shows that public complaints to the local government varied. However, the complaints handling mechanisms became an efficient instrument which the mayor used in monitoring the performance of his sub-ordinates.